Review on Haploidentical Hematopoietic Cell Transplantation in Patients with Hematologic Malignancies - William A. Fabricius; Muthalagu Ramanathan (Advances in Hematology)
Allogenic hematopoietic cell transplantation (HSCT) is typically the preferred curative therapy for adult patients with acute myeloid leukemia, but its use has been reduced as a consequence of limited donor availability in the form of either matched-related donors (MRD) or matched-unrelated donors (MUD). Alternative options such as unrelated umbilical cord blood (UCB) transplantation and haploidentical HSCT have been increasingly studied in the past few decades to overcome these obstacles. A human leukocyte antigen- (HLA-) haploidentical donor is a recipient’s relative who shares an exact haplotype with the recipient but is mismatched for HLA genes on the unshared haplotype. These dissimilarities pose several challenges to the outcomes of the patient receiving such a type of HSCT, including higher rates of bidirectional alloreactivity and graft failure. In the past 5 years, however, several nonrandomized studies have shown promising results in terms of graft success and decreased rates of alloreactivity, in part due to newer grafting techniques and graft-versus-host disease (GVHD) prophylaxis. We present here a summary and review of the latest results of these studies as well as a brief discussion on the advantages and challenges of haploidentical HSCT.